Las funciones del prefijo ex- en el español moderno - Menaker, Angelika (Verbum – Analecta Neolatina, 2011)
This paper analyzes the Modern Spanish prefix ex-. We discuss the role it plays in the meanings of various verbs. We compare prefixed verbs with basic verbs and verbs prefixed with ex- with those which have other prefixes.